(untitled) (diségno, 2019)
I regard architectural drawing as not just a means of communication, but also an important way to study the contemporary urban setting. It helps me think about what architecture is today, in an age when the multivectoral nature of architecture’s development has reached its apogee. Drawing is a path to oneself and to understanding what is happening around you and what you like in architecture. Here, of course, I cannot entirely separate my practice as a draughtsman from my main job: in terms of end result, drawing and architecture are very different from one another, but the two types of activity are based on reflections on one and the same subject – how to make cities interesting today, how to create mises-en-scène which in terms of quality and visual intrigue are a worthy match for the best examples offered by history. (read more)